IKLAN ROKOK A MILD VERSI BUKAN “BASA BASI”, TEMA “TANYA KENAPA”: ANALISIS PASCASTRUKTURAL - Sugeng Purwanto (Universitas Stikubank (UNISBANK) Semarang, 2010)
The study currently investigated A Mild Advertisements of Bukan Basa Basi Theme and Tanya Kenapa Tagline in terms of hermeneutic, semantic, symbolic, narrative and cultural codes on the basis of Ronald Barthes’ Post Structural Theoretical Framework. It turns out that A Mild Advertisements have loaded social criticisms, following the post Soeharto era in which people began to have the guts to say something, not afraid of being detained by military personnel. Say for example, one A Mild advertisement says “Siang Ditahan, Malam Balas Dendam” (Refrained at daytime, Revenged at night). Literally, this is a reflection of people during the fasting month in which they may eat in a double volume at night. However, on further deep interpretation, the sentence may mean people kept silent during Soeharto’s regime, and began to shout upon resignation of Soeharto. Finally, there is always a message—implicitly though—“Just smoke one or two cigarettes of A Mild to relieve tension.” This is the only truth (not basa-basi), but don’t ask me why. In conclusion, we need to thank A Mild for its social criticisms regarding human behaviors. Unfortunately, such credits have not adequately awarded to A Mild cigarette. It is also suggested that other products take A Mild’s steps, not directly influence people to buy the products. With this, people would appreciate more. Key words: hermeneutic, semantic, symbolic, narration, cultural codes, post structural